Disparities in financial literacy, pension planning, and saving behavior - Tabea Bucher-Koenen; Andreas Hackethal; Johannes Kasinger; Christine Laudenbach (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Financial literacy affects wealth accumulation, and pension planning plays a key role in this relationship. In a large field experiment, we employ a digital pension aggregation tool to confront a treatment group with a simplified overview of their current pension claims across all pillars of the pension system. We combine survey and administrative bank data to measure the effects on actual saving behavior. Access to the tool decreases pension uncertainty for treated individuals. Average savings increase|especially for the financially less literate. We conclude that simplification of pension information can potentially reduce disparities in pension planning and savings behavior.
Keywords: D14; G11; G51; G53; 330; saving behavior; retirement planning; digital planning tool